The exponential effects of empowering teenage girls - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
On July 11, 2016, the international community will observe World Population Day, and this year’s theme is “Investing in teenage girls.” Evidence has shown that empowering adolescent girls can break the cycle of poverty for themselves and for their families. It is the aim of this year’s World Population Day to emphasize the importance of allocating more resources to improve the opportunities available to adolescent girls.